2013
DOI: 10.1063/1.4812788
|View full text |Cite
|
Sign up to set email alerts
|

Protein electron transfer: Dynamics and statistics

Abstract: A statistical-mechanical analysis on the hypermobile water around a large solute with high surface charge density J. Chem. Phys. 130, 014707 (2009) Electron transfer between redox proteins participating in energy chains of biology is required to proceed with high energetic efficiency, minimizing losses of redox energy to heat. Within the standard models of electron transfer, this requirement, combined with the need for unidirectional (preferably activationless) transitions, is translated into the need to minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(130 citation statements)
references
References 122 publications
(193 reference statements)
7
122
1
Order By: Relevance
“…A significant mechanistic question relevant to protein electron transfer is what are the interaction mechanisms influencing the breadth of the fluctuations (statistics) and what are the relevant time-scales (dynamics). [4][5][6] Both questions are essential for the modeling of the electron-transfer rates. Clearly, the amplitude of the fluctuations affects the reaction activation barrier.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant mechanistic question relevant to protein electron transfer is what are the interaction mechanisms influencing the breadth of the fluctuations (statistics) and what are the relevant time-scales (dynamics). [4][5][6] Both questions are essential for the modeling of the electron-transfer rates. Clearly, the amplitude of the fluctuations affects the reaction activation barrier.…”
mentioning
confidence: 99%
“…The connection between the first and second moments is lost and two reorganization energies, λ St and λ, are required. 6 One still has the condition of crossing of two parabolas in Eq. (1) at X = 0, which results in the relation ⟨X⟩ i = κ G ∆F 0 ± λ, where the same convention as above applies to the ± sign and κ G = λ/λ St .…”
mentioning
confidence: 99%
“…The local structure of water molecules at interfaces is, for example, well known to be partly ordered. Recently, Matyushov et al [47][48][49][50] have explored how experimentally rather smaller reorganisation energies than expected from atomistic simulations might be explained, examining the case [47] of cytochrome c. They extend the Marcus/Gerischer model to distinguish between two types of reorganisation energy representing medium polarisation and (a typically large) thermal fluctuation contribution, the latter being linked to a heterogeneous region surrounding the protein cofactor. The arguments are interesting and would perhaps apply a fortiori to the local geometry of the EC-STM set up.…”
Section: Current Developmentsmentioning
confidence: 99%
“…The superscript St refers to the fact that this reorganization energy equals half the Stokes shift DX [46,47]. Finally one can define the reorganization energy k r as the work to bring the system to the equilibrium geometry of the final state.…”
Section: Connections With Microscopic Simulationsmentioning
confidence: 99%
“…In charge migration over multiple fragments such freezing of nuclear modes can lead to non-equilibrium effects as seen for example in the case of DNA photolyase by direct FB-DFTB/MD simulations [41]. Matyushov and co-workers developed a consistent set of tools and concepts to comprehend ET in non-ergodic biological systems [47,115,119]. Looking again at their study of the photoreactive center (see previous sub-section), they showed that the reorganization energy calculated from the width of the energy gap fluctuations largely exceeded that calculated by the Stoke shift (k var ) k St ), enabling the ET process to take place in a near activation-less manner.…”
Section: Non-ergodic Systemsmentioning
confidence: 99%